Challenges encountered by teachers and pupils in increasing precision and writing consistency of government primary early graders in Tanzania - Legnath Ambrossy Lukuwi; Abdallah Jacob Seni (Освітній вимір, 2025)
The current study examined teachers’ challenges in enhancing the writing competencies of government primary school children and ways to mitigate the challenges. Mixed methods and case study design were used with 88 participants from eight government primary schools in Namtumbo District. A purposeful sample of 16 teachers, 8 headteachers, and 64 Standard I and II pupils was made. Classroom observation, unstructured interviews, focus group discussions, document reviews, questionnaires, and checklists were utilised during data collection. Quantitative information was analysed through SPSS, and thematic analysis was done on qualitative information. Study findings indicate that teachers faced several challenges, including overcrowded classrooms, insufficient teaching and learning facilities, inadequate teachers’ houses and classrooms. The strategies to address the challenges include using technology and innovative pedagogies, such as learning corners. These findings imply the need to provide teachers with teaching materials and in-service professional development to enable them to use contextually available technologies to mitigate the noted challenges.